« Ascénir » le space opera : de Joël Maillard à Bruno Latour - Danielle Chaperon (ReS Futurae)
The hypothesis developed around Quitter la Terre (2017, Lausanne, Théâtre de l'Arsenic) questions in its own way "the idea that SF would not find its "privileged mode of realization" in the theater". (Bionda, 2019). This questioning is rooted in the observation that this show shares with several other recent productions an apparently incongruous motif: touch down, namely the action of landing an aerospace vehicle on the ground of a planet. This motif is analyzed in relation to the imperative of "return to Earth", addressed by Bruno Latour in his lecture-show Inside (2016, Paris, Théâtre Nanterre-Amandiers). The verb ascénir, displayed in the title of the article, proposes to gather some modalities of this operation. The verb ascènir, which is used in the title of the article, is intended to bring together a few of the modalities of this operation. Written by Julie Sermon(2018), which is part of an eco-theatrical movement that aims to decentralize human beings, Quitter la Terre (2017) does not propose to "eliminate them from the stage, to confront them with non-humans, or to place them back within a spatio-temporal scale that exceeds them and relativizes their place" (Lehmann,2002). In an artistic context marked by the debates around the anthropocene,Joël Maillard attacks the "cosmos of the moderns" by diverting certain imaginations from the science fiction of the 1960s and 1970s and, following the example of Bruno Latour, by making the stage cage the symbolic stake of a "War of the Worlds".